Processing of Gayam Fruit as Mochi Filling - Putra, Fajar Dharma; Pratama, Muhamamd Daffa; Wowor, Wulanmeiaya (Journal of Industrial Engineering & Management Research, 2022)
Gayam is a tree-shaped plant that has uses as a food product, especially its fruit seeds. Gayam is on a branch of the Gayam tree. Usually Gayam is only processed by boiling and frying it. the goal is to process whether Gayam fruit can be processed into stuffing in Mochi. The type of research used is development research. Development research is a research method that produces finished products in the form of products and tests the effectiveness of these products. In this study, the researcher used a procedural research method. A procedure is an action or activity stage to complete a process. The research procedure starts with the preparation, implementation and final process in making Mochi Stuffing using Gayam fruit. The desired browning also gets a good thing because the natural color is given from the Gayam fruit itself. is close to perfect. So it can be said that the research on processing Gayam fruit as a mochi filling has been successful and is suitable for consumption.